SMEs fintech financing: does board governance matter? - zakaria, zuriawati; Kuah, Yoke Chin (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
The purpose of this study is to examine the board governance factors that influence a small and medium enterprise’s (SME’s) decision toward fintech financing. A structured questionnaire survey of 90 Malaysian SMEs was used and the data analyzed using the Heckman selection model and the marginal effect model. The results demonstrate that SMEs’ female board members, family board members, and the duality of their CEOs have a significant influence on their decision to obtain financing from fintech platforms. Professional services provided by experts have a negative influence on their decisions to engage in fintech financing. The SMEs’ board size, the length of their chairmen’s service, and non-family board members are negatively related to their decisions to apply for financing. The more male members that were on the board, the more likely the SME was to choose to apply for external financing during the survey year.